New records of Pantophthalmidae (Diptera: Brachycera) from Northeast Brazil - Soares, Matheus Mickael Mota; Fachin, Diego Aguilar; Machado, Ronald de Andrade; Ale-Rocha, Rosaly (EntomoBrasilis, 2023)
Although Pantophthalmidae are widespread in the Neotropical Region, only three of 20 species of the family are known in the Northeast region of Brazil: Pantophthalmus planiventris (Wiedemann, 1821), Pantophthalmus tabaninus Thunberg, 1819, and Pantophthalmus vittatus (Wiedemann, 1828). In this paper, we record, for the first time, Pantophthalmus comptus Enderlein, 1912 from the state of Maranhão, in area of state covered by Amazon Forest biome, and Pantophthalmus pictus (Wiedemann, 1821) from the state of Pernambuco, near the coast, within the Atlantic Forest biome. These two species have been reported elsewhere from Brazil and now their distribution has expanded to the Northeast. Also, we provide images of a female specimen of P. planiventris, known, in the Northeast region of Brazil, from the state of Maranhão only, and of the male terminalia of P. comptus. This paper increases the number of known species of Pantophthalmidae from the Northeast Brazil to five species.